Flywheel batteries come around again. - Hebner, R.
Today's flywheel batteries, embody technological advances, and they are serious contenders for a variety of important energy-storage applications. They are, for example, competitive with chemical batteries in applications like transportation or improving power quality, which involve many charge-discharge cycles and little in the way of long-term storage. Progress in power electronics, particularly in high-power insulated-gate bipolar transistors (IGBTs) and field-effect transistors (FETs), underlies higher-power flywheel operation. While the stored energy is determined by the speed, mass, and geometry of the wheel, the limits on input and output power are in general set by the power electronics. With these higher power devices, fewer individual components are needed, so the power electronics package can be comparable in size to the flywheel plus motor-generator combination. This paper describes the main features of flywheel energy storage systems and space, hybrid electric vehicle, and combat vehicle applications
Keywords: Charge-discharge cycles; Combat vehicles; Energy-storage applications; Flywheel batteries; Flywheel plus motor-generator combination; High-power FET; High-power IGBT; Hybrid electric vehicles; Power electronics; Power quality improvement; Space applications